PENINGKATAN EFEKTIVITAS PEMBELAJARAN MELALUI PENGUASAAN KETERAMPILAN MENGAJAR MEMBIMBING DISKUSI KELOMPOK KECIL, MENGELOLA KELAS, DAN MENGAJAR KELOMPOK KECIL SERTA PERORANGAN - Citra Septyani Zuhrotunnisa; Eka Septiana Nakiya Khusna; Nazilatun Nisa; Ardita Putri Chahyani; Zulfadewina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article examines in depth eight essential teaching skills for primary school teachers as part of their professional competence in effective learning practices. The teaching skills include: (1) small group discussion skills, (2) classroom management skills, and (3) small group and individual discussion skills. The research method used is a literature study that relies on written sources as the main data source, without collecting field data. Data sources were analyzed from various scientific journals, textbooks, and relevant education policy documents, especially those published in the last five years. The results of this study show that it is crucial to acquire teaching skills for learning effectiveness. This is particularly important in the context of basic training which emphasizes a holistic central approach. Moreover, these skills connect and shape the entire learning cycle. The findings are expected to be a reference for PGSD students and educators in the development of reflexive and adaptive learning practices.